Weight status, BMI and physical fitness in polish youth: relationships between 1986 and 2016 - Bartkowiak, Sylwia (2022)
One of the components affecting the level of health is physical fitness and diets, which is also considered the foundation of a healthy lifestyle. Methods: Samples by survey ranged from 871 to 1,417 (boys) and from 843 to 1,326 (girls). Speed (5 m run), agility (figure-8-run), explosive power (vertical jump), flexibility (stand and reach) and cardiovascular fitness (step test) were measured. The Body Mass Index (BMI) of each student was classified as Thin, Normal weight or Overweight/Obese (Owt/Ob) relative to International Obesity Task Force (IOTF) criteria. Fitness items were compared among weight status groups and across surveys with sex-specific analyses of covariance. Regressions of each fitness item on the BMI in the four surveys were done using linear and nonlinear quadratic models. Results: Performances on all fitness tests except flexibility were poorer among Owt/Ob compared to Normal and Thin youth, but performances on fitness tests within weight status groups did not differ consistently across surveys. Conclusions: Relationships between the BMI and fitness tests varied across surveys, but suggested reasonably consistent curvilinear relationships between fitness tests and the BMI among boys more so than girls.